Strategies to reduce limb ischemia in peripheral venoarterial extracorporeal membrane oxygenation: A systematic review and Meta-analysis. (15th August 2022) - Marbach, Jeffrey A.; Faugno, Anthony J.; Pacifici, Stefano; Chweich, Haval; Marbach, Jennifer K.; Rabinowitz, Judy B.; Thayer, Katherine L.; Di Santo, Pietro; Kapur, Navin K.
Abstract: Venoarterial extracorporeal membrane oxygenation (VA-ECMO) provides cardiovascular and respiratory support for patients in cardiogenic shock; yet, complications are a frequent source of morbidity and mortality. Limb ischemia can be potentially mitigated by limp perfusion protection strategies (LPPS). We performed a systematic review and meta-analysis to evaluate the safety and efficacy of two LPPS in patients treated with peripheral VA-ECMO – prophylactic insertion of a distal perfusion catheter (DPC) and small bore (<17 Fr) arterial return cannula. Among 22 included studies, limb ischemia was reduced in patients receiving a small arterial cannula (OR 0.40, 95% CI 0.24–0.65; p < 0.001) and in patients receiving a prophylactic DPC (OR 0.31, 95% CI 0.21–0.47; p < 0.001). Mortality was not significantly reduced with either a small arterial cannula (OR 0.70, 95% CI 0.23–2.18; p = 0.54) or prophylactic DPC strategy (OR 0.89, 95% CI 0.67–1.17; p = 0.40). As such, prophylactic insertion of a DPC or smaller bore arterial return cannula appear to reduce the risk of lower limb ischemia in this analysis. Further data are needed to confirm these findings. Registration: Registered in PROSPERO Database (Registration CRD42020215677). Highlights: In patients treated with VA-ECMO limb complications are a frequent source of morbidity and mortality. Limb perfusion protection strategies may reduce limb complications in VA-ECMO. Patients receiving small arterial return cannulas (<17 Fr) had reduced rates of limb ischemia (OR 0.40, 95% CI 0.24–0.65; p ≤0.001). Patients receiving prophylactic distal perfusion catheters had reduced rates of limb ischemia (OR 0.31, 95% CI 0.21–0.45; p < 0.001). Neither limb perfusion protection strategy evaluated impacted mortality.